Effects of psychosocial stress on prosociality: the moderating role of current life stress and thought control - Hensel, Lisa; Rohleder, Nicolas; Niessen, Cornelia (Stress. The International Journal on the Biology of Stress, 2022)
To date, only a few studies have examined whether and when stressed individuals are still prosocially motivated and willing to help others, which is in contrast to the relevance and importance that helping others has for our society. The present study investigates the impact of affective and biopsychological acute stress responses on prosociality (prosocial motivation, helping behavior) under controlled laboratory conditions. In addition, it was examined whether this relationship is affected by individuals' current life stress and the cognitive ability to keep stress-related thoughts at bay. To induce acute stress responses (heart rate, negative affect, salivary alpha-amylase, cortisol), 55 individuals (28 women, M = 24 years old, SD = 4.53) were exposed to the Trier Social Stress Test (TSST). Current life stress (cortisol) was assessed over two days of participants' everyday lives. Thought control ability was assessed with the think/no-think paradigm and was additionally manipulated after the acute stress intervention (TSST) via instructions. The results showed that acute stress was positively associated with prosociality. Specifically, negative affect was positively related to prosocial motivation and salivary alpha-amylase was positively associated with helping behavior. Current life stress moderated the relationship between salivary cortisol and helping behavior: the association was positive at low levels of current life stress. The instruction to control one's thoughts but not participants' general ability to do so reduced stress responses (negative affect). In sum, the findings suggest that prosociality increases following acute stress and that this effect depends on the level of current life stress. Additionally, adopting the strategy of controlling stress-related thoughts was found to be promising for attenuating individuals' stress responses.
CRIS-Team WoS Importer:2022-07-01

INSELpro: Ein elektronischer Marktplatz für personennahe Dienstleistungen - Hensel, Lisa; Henselmann, Daniel; Hofmann, Jan (Personennahe Dienstleistungen der Zukunft, 2023)
Im BMBF-geförderten Verbundprojekt INSELpro bieten Prosumer ihre Dienste auf einem Markt der örtlichen Nachbarschaftsdienstleistungen an. Hilfebedürftigen Mitbürgern in einem geografischen Quartierbereich werden über eine Dienstleistungsplattform zu ihrer jeweiligen Unterstützungsanforderung passende Helfer vermittelt, die sich grundsätzlich dazu bereiterklärt haben, Hilfe zu leisten. Angebot und Nachfrage werden über die Plattform zusammengeführt, die Dienstleistungen aber extern zwischen den Beteiligten konkretisiert und ausgeführt. Die Besonderheit ist dabei, dass die Vermittlung mithilfe einer flexiblen Matrix aus benötigten und vorhandenen Fähigkeiten erfolgt, was die Vermittlungsqualität verbessert. Das Forschungsprojekt setzt auf den wissenschaftlichen Ansatz des Prototyping, bei dem ein Artefakt (hier: die Vermittlungsplattform mit einer App als Frontend) in mehreren iterativen Zyklen entwickelt wird. Dabei sind jeweils nutzerzentrierte Evaluationen direkt an die einzelnen Entwicklungsschritte angekoppelt, um ggf. Fehlentwicklungen frühzeitig gegensteuern zu können. Um die Beteiligung an dieser elektronisch unterstützten und koordinierten Art der Nachbarschaftshilfe auszubauen bzw. auf einem hohen Niveau zu halten, sind unterschiedliche Maßnahmen denkbar. Der vorliegende Beitrag zeigt Ansätze zur Incentivierung der beteiligten Prosumenten auf, die sowohl online als auch offline durchführbar sind.<br
Keywords: Dienstleistung; Prosument; Motivation; Anreizsetzung; Zuordnung; Algorithmus; Evaluation

Meta-analytic evidence shows no relationship between task-based and self-report measures of thought control - Göbel, Kyra; Hensel, Lisa; Schultheiss, Oliver; Niessen, Cornelia (Applied Cognitive Psychology, 2022)
We meta-analytically examined correlations between task-based and self-report thought control measures as well as potential moderators. Results of a frequentist meta-analysis indicate that the two measures do not overlap, r =.07, 95% CI [−0.01;0.15] (k = 20; N = 1194); subgroup analyses for different self-report measures r =.12; 95% CI [−0.06;0.30] and r =.03, 95% CI [−0.05;0.11], respectively. Additionally, we found no evidence for the presence of moderators. To further test whether the identified effect size is more consistent with a null effect or the assumption of a positive association, robust Bayesian meta-analyses were conducted. We did not obtain sufficiently strong evidence to decide for or against a null effect. In sum, our findings suggest that task-based and self-report thought control measures might capture different psychological processes and thus call for more research on the different underlying processes and constructs they measure.
CRIS-Team Scopus Importer:2022-05-13
Keywords: Bayesian meta-analysis; meta-analysis; think/no-think; thought control; thought suppression